Public Relations Communication Strategy in Building the Image of an Environmentally Friendly Hotel: an Analysis of Greenotel Cilegon - Rina Fitriana; Muhammad Jaiz; Nina Yuliana; Asih Kurnianingsih; Nuryadina Augus Rini (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
The increasingly competitive hospitality industry encourages each hotel to build strong differentiation, including through the formation of a brand image relevant to sustainable values. Greenotel Cilegon as a three-star hotel carries an environmentally friendly (go green) concept in the middle of the industrial area of ​​Cilegon City, thus requiring an effective Public Relations communication strategy to strengthen this image. This study aims to analyze the Public Relations communication strategy in shaping the image of an environmentally friendly hotel at Greenotel Cilegon. Using a qualitative approach with a case study method, data was obtained through in-depth interviews, field observations, and documentation, then analyzed through the process of data reduction, data presentation, and drawing conclusions. Information Integration Theory is used as a foundation in understanding the process of forming public perception. The results show that Greenotel Cilegon's Public Relations communication strategy is carried out through consistent social media content management, publication of environmentally oriented activities, utilization of travel e-commerce platforms, and the creation of hotel space experiences that highlight sustainable values ​​through recycled material designs. This strategy is proven to strengthen brand associations related to the uniqueness of the go green concept, natural aesthetic values, and commitment to the environment, thus supporting the formation of a positive image in the public mind. This study confirms that the success of an eco-friendly hotel image is determined by the consistency of communication messages and the alignment between symbolic communication and the real experiences received by visitors